2017
DOI: 10.1111/jpn.12797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein levels and 2‐methylbutyrate on ruminal fermentation, nutrient degradability, bacterial populations and urinary purine derivatives in Simmental steers

Abstract: The objective of this study was to evaluate the effects of dietary crude protein (CP) levels and 2-methylbutyrate (MB) supplementation on ruminal fermentation, bacterial populations, microbial enzyme activity and urinary excretion of purine derivatives (PD) in Simmental steers. Eight ruminally cannulated Simmental steers, averaging 18 months of age and 465 ± 8.6 kg of body weight (BW), were used in a replicated 4 × 4 Latin square design by a 2 × 2 factorial arrangement. Low protein (98.5 g CP/kg dry matter [LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Further investigation of the interaction indicates that ammonia concentration for LF-IA was greater compared with LF-C. Ruminal ammonia concentrations in response to IA are likely related to dietary protein supply. For example, Wang et al (2018) observed an interaction between 2-methylbutyrate supplementation and dietary protein levels (10 and 13% on a DM basis) in steers. With the low-protein diet, ruminal ammonia concentration was lower when 2-methylbutyrate was supplemented, but this did not occur with the high-protein diet.…”
Section: Main Effect Of Ia Within the Lf Dietsmentioning
confidence: 99%
“…Further investigation of the interaction indicates that ammonia concentration for LF-IA was greater compared with LF-C. Ruminal ammonia concentrations in response to IA are likely related to dietary protein supply. For example, Wang et al (2018) observed an interaction between 2-methylbutyrate supplementation and dietary protein levels (10 and 13% on a DM basis) in steers. With the low-protein diet, ruminal ammonia concentration was lower when 2-methylbutyrate was supplemented, but this did not occur with the high-protein diet.…”
Section: Main Effect Of Ia Within the Lf Dietsmentioning
confidence: 99%
“…Improved digestibility of NDF and NDF responsive to MI makes more fermentation metabolites, such as VFAs, available in the rumen. For example, Wang et al (2018b) found that supplementation with 16.8 g of 2-methylbutyrate per steer per day increased the molar ratio of effectively degradable NDF and rumen acetate. Similar results were observed in this study, suggesting that supplementation with 0.3% MI could significantly improve the apparent digestibility of NDF and ADF, thereby increasing the ADG and ADMI in yaks.…”
Section: Discussionmentioning
confidence: 99%